Developing Interactive E-LKPD with Wizer.Me: A Needs Analysis for Enhancing Poetry Writing Skills in Junior High School Students in Palembang - Muhammad Edwin; Zahra Alwi; Izzah Izzah (STAI Hubbulwathan Duri, 2025)
Writing skills are crucial in Indonesian language learning at the secondary school level. However, students’ creative writing abilities remain weak, and low motivation is often cited as a contributing factor. Therefore, an effective solution is needed to support creative writing instruction. This study aimed to analyze students' needs for an Electronic Learner Worksheet (E-LKPD) to enhance creative writing skills in junior high school. A survey method was employed, involving 294 students. Data were collected through questionnaires and interviews, and analyzed using both qualitative and quantitative techniques. The findings revealed three main points: (1) the E-LKPD should align with established principles of E-LKPD development, its characteristic features, and the fundamentals of poetry writing instruction; (2) existing E-LKPD exhibit significant shortcomings; and (3) teachers at Junior High School 56 Palembang express a strong need for interactive E-LKPD to support poetry writing instruction. The study underscores the necessity of developing more effective and engaging E-LKPD to improve students’ creative writing skills and overall literacy. Enhancing the quality of instructional materials could better motivate students and foster greater achievement in writing.